Game design analysis of the video game Abzu - Ruiz Leyva, Daniel (2017)
ABZU is a single player game developed by Giant Squid studios for ?box One, P54 and Microsoft Window's 7 systems, Exploration and discovery are the central themes. The game can be described as '"a swimming simulation that shows a dream-like interpretation of the ocean's beauty" (Thielenhaus, 2016). The game takes place in an oceanic world, inhabited with real-world simulated animals. The game space is a tree dimensional map, divide in small sections. Each section can only be explored once in the story line. The game objective is not explicitly mentioned; it can be interpreted as restoring the ocean's life by releasing animals back to it. The only procedure to achieve the objective is exploration. Duringthegame, the player controls a humanoid character that resembles a futuristic scuba diver and whose origin and purpose remain unknown until the end of the game. Details in the landscape, like paintings and remnants of an ancient civilization, allow the player to create its own interpretation of the backstory. As the game progresses a story about this diver, a white shark and their relation with the ocean is told. The story is divided in five "chapters" which take place in different map areas distinguished by new ocean environments. The progression through the game space and the story is parallel and liner, While exploring a part of the world, events that form the plot are showed through short cut scenes. Usually, these scenes are delivered as transitions between map areas. The game ends with the story.